Hubungan Simultan Bank-Firm Relationship dan Kinerja pada Perusahaan Socially Responsible Investment (SRI) di Indonesia - Zusryn, Alyta Shabrina; Innayah, Maulida Nurul; Sahulata, Hanastasya (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2020)
A bank-firm relationship in the company occurs when the bank as a lender can obtain more extensive information from other parties. This study aims to examine the simultaneous relationship between bank-firm relationships and company performance. The sample in this study is non-financial socially responsible investment (SRI) firms listed on the SRI KEHATI index. The data analysis method uses two-stage least square (2SLS). The results of this study found that only multiple-bank relationships had a positive and significant effect on company performance. In addition, the company's performance also influences the company's decision to conduct multiple-bank relationships. These results indicate a simultaneous relationship between multiple-bank relationships and the performance of companies that implement socially responsible investment (SRI) in Indonesia. Multiple-bank relationships provide convenience to banks in monitoring companies. While other indicator such as company relations with foreign banks, domestic banks, the number of banks and the bank loan ratio (BLR) were not significant in the simultaneous relationship. The implication of this research is that a company can conduct multiple-bank relationships to diversify external funding sources, reduce credit constraints and reduce strategy failures.